Refinement of Perioperative Feeding in a Mouse Model of Vertical Sleeve Gastrectomy - Doerning, Carolyn M (J Am Assoc Lab Anim Sci, 2018)
Provision of liquid enteral nutrition (LEN) during the perioperative period is standard practice for rodents undergoing bariatric surgery, yet these diets are associated with several challenges, including coagulation of the liquid diet within the delivery system and decreased postoperative consumption. We investigated the use of a commercially available high-calorie dietary gel supplement (DG) as an alternative food source for mice during the perioperative period. C57BL/6J male mice were fed high-fat diet for 8 to 10 wk prior to surgery. The study groups were: vertical sleeve gastrectomy (VSG) +DG, VSG+LEN, sham surgery+DG, and sham+LEN. Food and water intakes, body weight, and body fat composition was monitored throughout the study. Mice that received DG lost significantly more weight preoperatively than those fed LEN. However, during the postoperative period, body weight, body fat composition, and water and caloric intake were similar among all experimental diet groups. Three mice in the VSG+LEN group were euthanized due to clinical illness during the course of the study. In summary, feeding a high-calorie DG to mice undergoing VSG surgery is a viable alternative to LEN, given that DG does not significantly affect the surgical model of weight loss or result in adverse clinical outcomes. We recommend additional metabolic characterization of DG supplementation to ensure that this novel diet does not confound specific research goals in the murine VSG model.